PROFESIONALISME PRAJURIT TNI AU KORP KOMUNIKASI NAVIGASI (STUDI KASUS PADA DEPOHAR 40 BANDUNG) - Dhani Ramadhona; Kemalsyah Kemalsyah; Khaerudin Khaerudin (Strategi Pertahanan Udara, 2023)
The maintenance Depot 40 or what so-called Depohar 40 is a unit having the responsibility to conduct the middle and heavy-level maintenance for communication, navigation tool, computer, simulator and specified electronic devices. In recent days, the task implementation, and the professionalism of Depohar personnel still could not be fully achieved as it is expected, so it requires research to study it. The research also describes the condition of the personnel capability, infrastructure and supporting equipment and also the integrity of the Depohar Personnel. Professionalism according to Longman (in Hasanah,2019) can also be interpreted as the behaviour, skills or qualities of a professional person. The research applies the qualitative and SWOT analysis, which has been formulated to be the selected called as diversification strategy as the result to implement the professionalism of the Depohar 40 Personnel. The result of the analysis is Strategy Diversification, meaning that the Depohar 40 organization is in a stable condition but faces a number of formidable challenges, so it is predicted that the institution will experience difficulties in carrying out daily activities if it only sticks to the previous strategy. Therefore Depohar 40 is advised to immediately expand its tactical strategy; so that the strategy will focus on using force to overcome the threats it faces. It is hoped that if this strategy is implemented, the professionalism of Depohar 40 soldiers can be realized soon